MIGRATION OF LYMPHOCYTES IN PLASMA CULTURES OF HUMAN LYMPH NODES - Lewis, Warren H. (The Rockefeller University Press, 1921)
1. Lymphocytes were usually the first cells to migrate out into the plasmic clot from explanted pieces of lymph nodes. 2. Their paths of migration were irregular but in general they proceeded away from the explant. 3. The lymphocytes migrated at rates varying from 0.03 to 0.0013 mm. per minute. The rate of any one varied from minute to minute, and they often came to rest for varying lengths of time. 4. The migrating lymphocytes were very much elongated, with the nucleus always near the anterior end. The elongated tail contained the endoplasm with a few granular mitochondria and usually a few granules which took up neutral red. 5. The lymphocytes in cultures made from normal and pathological lymph nodes in auto and homoplasma showed no differences.